First record of the moray eel Gymnothorax reticularis, Bloch, 1795 in the Mediterranean Sea, with a note on its taxonomy and distribution - Stern, Nir; Goren, Menachem (Zootaxa, 2013)
The first Red-Sea Indo-Pacific alien moray eel in the Eastern Mediterranean is reported here. A single specimen of Gymnothorax reticularis was captured by a commercial bottom-trawl vessel off the northern coast of Israel. Morphological and anatomical similarities with the single known Red-Sea specimen raise an old taxonomic dilemma.